Roadway Support in Deep “Three-Soft” Coal Seam: A Case Study in Yili Mining Area, China - Wenxin Li; Jinxiao Liu; Lianjun Chen; Zhilu Zhong; Yongle Liu (Shock and Vibration)
This paper analyzes the large deformation of roadway in three-soft coal seam under the influence of tectonic stress. Taking the auxiliary conveying uphill roadway in Yili No. 1 Coal Mine as the engineering background, the deformation and failure mechanism of the surrounding rock and the supporting technology were studied. First, the characteristics of stress field and the surrounding rock properties of deep mining area were investigated through geostress measurement and rock mechanical test. Then, the roadway deformation and the loose circle of the supporting structure were obtained. Based on the results from measurement and theoretical analysis, we proposed a concept, i.e., “Stress adjustment-Strengthening-Grouting-Secondary support.” A numerical model was established to analyze the stress distribution and the state of plasticity in the surrounding rock. According to the results of the geostress measurement and the numerical simulation, a combined support scheme was proposed, i.e., “Yielding bolt & Shotcreting” as the primary support and “Prestressed grouting anchor cable & U-shaped shed” as the secondary support. Finally, the underground practice showed that the proposed support scheme can effectively control the large deformation and maintain the long-term stability of the roadway in deep and three-soft coal seam. The proposed technology has guiding significance for the support design under similar mining conditions.